2013
DOI: 10.1111/bij.12032
|View full text |Cite
|
Sign up to set email alerts
|

Western European Quaternary lions: new working hypotheses

Abstract: Cave lions (Panthera spelaea), which spread throughout Western Europe for several thousand years, disappeared approximately 14 000–14 500 years ago. They were supposedly replaced by modern lions (Panthera leo) approximately 8000 years ago. Modern lions reached the steppes of Ukraine and Hungary, without penetrating the forests of Central Europe. The present study focuses on Italian and Spanish findings that possibly bridge the alleged absence of these big cats from Europe for 6000 years. Fossil lion remains fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Our models predict that large areas of Europe could become climatically suitable for leopards by 2050, particularly for the Persian leopard. During the Pleistocene, several large carnivores were found in Europe, including wolves, Canis lupus , bears, Ursus spelaeus and Ursus arctos , leopards, Panthera pardus , lions, Panthera fossilis and Panthera spelaea , and hyena, Crocuta crocuta spelaea (Masseti & Mazza, 2013 ; Paijmans et al., 2018 ). The little‐known European Ice‐Age leopard, P. p. spelaea , occurred across Europe until 17,000 years ago, southern Europe until ~11,000 ya and in the Balkans until 9000 ya (Sommer & Benecke, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our models predict that large areas of Europe could become climatically suitable for leopards by 2050, particularly for the Persian leopard. During the Pleistocene, several large carnivores were found in Europe, including wolves, Canis lupus , bears, Ursus spelaeus and Ursus arctos , leopards, Panthera pardus , lions, Panthera fossilis and Panthera spelaea , and hyena, Crocuta crocuta spelaea (Masseti & Mazza, 2013 ; Paijmans et al., 2018 ). The little‐known European Ice‐Age leopard, P. p. spelaea , occurred across Europe until 17,000 years ago, southern Europe until ~11,000 ya and in the Balkans until 9000 ya (Sommer & Benecke, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among large felids, leopards may be the best candidate for expansion into Europe, despite lions persisting in Europe for longer (Masseti & Mazza, 2013 ). Leopards are solitary, with a wide niche breadth and are highly adaptable, even in human‐dominated landscapes (Athreya et al., 2016 ; Braczkowski et al., 2018 ; Stein et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the cave lions were dependent on the availability of large and mostly moderately fast-moving prey (Bocherens et al 2011;Diedrich 2014Diedrich , 2017Bocherens 2015). The evolving climate and vegetation during the Late Pleistocene promoted habitat fragmentation (Huntley 1988(Huntley , 1990(Huntley , 1992Starkel 1991;Grove and Rackham 2001;Magri et al 2007;Masseti and Mazza 2013); and the patches of Pleistocene vegetation acted as refugia for the Pleistocene fauna (Stewart and Lister 2001;Reumer 2007). Populations enclosed in these fragmented habitats reacted to environmental changes by evolving towards smaller-bodied members.…”
Section: Extinction Of Panthera Spelaea: the King Is Deadmentioning
confidence: 99%
“…The artefact probably depicts a lion head and so may serve as indirect proof of the species presence in the region. This maneless lion would be a characteristic element of cave paintings and many Holocene artefacts, even though the maned lions dominated in the art of this period (Capitan et al 1924;Friant 1940;Hemmer 1967;Spassov and Stoychev 2005;Masseti and Mazza 2013).…”
Section: Holocene Panthera Leo Of Ukraine: Long Live the Kingmentioning
confidence: 99%
“…Finally, the latest dhole occurrences and stratigraphic time provide indicate that an abrupt increase of the human population and hunting activity during the latest Pleistocene and early Holocene could be treated as one of the factors leading to the extinction of C. alpinus . Recent research has revealed that increases of the human population coincided with the vanishing and final extinction of many large European carnivores such as the lion (Masseti and Mazza, 2013). However, during the time when the dhole became extinct in Europe, human impact was still relatively low.…”
Section: The Evolution Of Cuon Alpinus In the Middle–late Pleistocene Of Europe: Possible Impact Of Other Large Canidsmentioning
confidence: 99%